Electric machines : steady state, transients, and design with MATLAB. - Boldea, Ion, 1945-; Tutelea, Lucian, ....- (Boca Raton : CRC, 2010)
Ubiquitous in daily life, electric motors/generators are used in a wide variety of applications, from home appliances to internal combustion engines to hybrid electric cars. They produce electric energy in all electric power plants as generators and motion control that is necessary in all industries to increase productivity, save energy, and reduce pollution.With its comprehensive coverage of the state of the art, Electric Machines: Steady State, Transients, and Design with MATLAB® addresses the modeling, design, testing, and manufacture of electric machines to generate electricity, or in constant or variable-speed motors for motion control.The book is organized into three stand-alone sections' Steady State, Transients, and FEM Analysis and Optimal Design 'providing a complete treatment of electric machines, which includes comprehensive coverage of:TopologiesSteady-state modeling and performancePreliminary design and testingModeling for transientsControl essentialsFinite element analysisOptimal design methodologiesThe book contains numerous computer simulation programs in MATLAB and Simulink®, available on an accompanying CD-ROM, to help readers make a quantitative assessment of various parameters and performance indices of electric machines. Skillfully unifying symbols throughout the book, the authors present a great deal of invaluable practical laboratory work that has been classroom-tested in progressively modified forms. This very capable textbook presents expressions of parameters, modeling, and characteristics that are directly and readily applicable for industrial R&D in fields associated with electric machines industry for modern (distributed) power systems and industrial motion control via power electronics.